2014
DOI: 10.1074/mcp.m113.032698
|View full text |Cite
|
Sign up to set email alerts
|

Label-free Quantitative Protein Profiling of vastus lateralis Muscle During Human Aging

Abstract: Sarcopenia corresponds to the loss of muscle mass occurring during aging, and is associated with a loss of muscle functionality. Proteomic links the muscle functional changes with protein expression pattern. To better understand the mechanisms involved in muscle aging, we performed a proteomic analysis of Vastus lateralis muscle in mature and older women. For this, a shotgun proteomic method was applied to identify soluble proteins in muscle, using a combination of high performance liquid chromatography and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 56 publications
5
35
1
2
Order By: Relevance
“…However, although these analyses are important for discovery of novel pathways with aging, it should be acknowledged that changes at the mRNA level are not always reflected at the level of proteins, and a greater divergence of results has been observed when proteomic approaches have been employed (Table 2). Theron et al (159) identified 35 proteins that were differentially expressed during aging, most of which were downregulated and involved in energy metabolism, the myofilament, or the cytoskeleton. In reviewing the literature, Baraibar et al (8) concluded that most proteomic studies reported decrements in key mitochondrial enzymes in aging muscle, although some investigators have indicated increased levels (Refs.…”
Section: Transcriptomic and Proteomic Mitochondrial Characteristics Omentioning
confidence: 99%
“…However, although these analyses are important for discovery of novel pathways with aging, it should be acknowledged that changes at the mRNA level are not always reflected at the level of proteins, and a greater divergence of results has been observed when proteomic approaches have been employed (Table 2). Theron et al (159) identified 35 proteins that were differentially expressed during aging, most of which were downregulated and involved in energy metabolism, the myofilament, or the cytoskeleton. In reviewing the literature, Baraibar et al (8) concluded that most proteomic studies reported decrements in key mitochondrial enzymes in aging muscle, although some investigators have indicated increased levels (Refs.…”
Section: Transcriptomic and Proteomic Mitochondrial Characteristics Omentioning
confidence: 99%
“…The predominant method has been 2-dimensional gel electrophoresis (2DGE) followed by in-gel trypsin digestion and tandem MS (MS/MS) (1416). More recently, 1-dimensional gel electrophoresis (1DGE) has been utilized in the characterization of normal, aging, and dystrophic skeletal muscle (1719). Although differentially expressed proteins in muscular dystrophy samples were identified using the 2DGE proteomic strategy, a number of technical shortcomings make the use of this approach impractical for the study of integral membrane proteins by MS/MS.…”
mentioning
confidence: 99%
“…The pathophysiological mechanisms of sarcopenia are believed to be highly complex resulting in a multi-factorial etiology. Recent proteomic studies have established extensive changes in the skeletal muscle proteome during the natural aging process [210,211,212], whereby gel-based proteomics has been instrumental in the initial cataloguing of the aged muscle proteome [213,214,215]. Skeletal muscle aging is closely associated with persistent impairments of the peripheral nervous system, which trigger excitation-contraction uncoupling and pathophysiological cycles of denervation and faulty reinnervation.…”
Section: Comparative Skeletal Muscle Proteomics Using Two-dimensiomentioning
confidence: 99%